PENERAPAN MODEL PROBLEM BASED LEARNING DENGAN PENILAIAN AUTENTIK PADA MATERI GETARAN, GELOMBANG, BUNYI, DAN CAHAYA TERHADAP KOMPETENSI IPA PESERTA DIDIK KELAS VIII SMP NEGERI 4 KUBUNG - Annisa Rahma Jelita; Festiyed Festiyed; Letmi Dwiridal (Universitas Negeri Padang, 2015)
This research described the application of Problem Based Learning (PBL) with authentic assessment to achieve the student’s competence in natural science. This research was conducted in SMPN 4 Kubung with taking learning material about vibration, wave, sound, and light. This research was done to solve the problem about the implementation of teacher centered learning. The students just write and listen what is presented by teacher so it can affect to the student competence. Type of research was quasy experimental research with randomized control group only design. The population were the students grade VIII SMPN 4 Kubung in the 2014/2015 academic year with sampling technique was purposive sampling. This research used three instruments, those are test sheet of knowledge competence, self assessment sheet of attitude competence, and performance sheet of skill competence. The result of this research could be presented based on data analysis. First, the class which use PBL models get average value in knowledge competence, attitude competence, and skill competence respectively 80.42, 89.29, and 91.96. Second, the use of PBL models has given significant effect toward science competency of students grade VIII SMPN 4 Kubung